Titik High Coffee Marketing Communication Strategy Through Instagram Social Media - Rahman, Mega Nur (Jurnal Indonesia Sosial Sains, 2024)
Titik High Coffee is a coffee shop with an industrial concept located on Jln. Bojong Koneng Atas Bandung. This research aims to find out the marketing communication strategy for Titik High Coffee via Instagram social media. The type of research used is descriptive with a qualitative approach. Researchers carried out objects and held direct interactions with informants, owners, marketing, consumers and observing social media on Instagram Titik High Coffee. The data analysis technique is carried out by gaining an understanding of the research focus, then drawing a conclusion in the form of a general understanding based on reality. The findings obtained from this research show that Titik High Coffee's marketing communication strategy through Instagram social media is effective as a promotional medium because most of the consumers who visit are Instagram social media users.